Sondeo sobre la comercializacion del frijol en Cusco - Ortíz, V.; Maître, Adrian (International Center for Tropical Agriculture, 1989)
Objectives were to facilitate the economic study of bean commercialization in Cusco, determine elements and criteria to guide bean production and improvement, and assess the degree of acceptance of 2 new var. in an informal survey with 10 traders. Bean production in Cusco has defined commercialization channels and self-consumption is nonsignificant. Grain of the same color is preferred: 70 percent yellow, 45 percent white, and 10 percent red. Prices are fixed accordingly. Market pressures exist regarding product uniformity and good quality. Important markets are Puerto Maldonado, Lima, Tacna, and Arequipa. Commercialization mainly takes place in the mo. of June-Aug. and Jan.-March. The Cusco bean market has grown over the past yr. Bean var. evaluated were ZAV 83099 and Blanco Sarkantay. Both are considered as good alternatives with greater grain uniformity, but var. ZAV 83099 should undergo additional cooking and organoleptic tests. (CIAT)